Clinical Features of Endogenous Endophthalmitis Secondary to Minimally Invasive Upper Urinary Tract Calculus Removal. (2nd January 2022) - Lou, Bingsheng; Sun, Yi; Lin, Jialiu; Yuan, Zhaohui; He, Liwen; Long, Chongde; Lin, Xiaofeng
ABSTRACT: Purpose: To evaluate endogenous endophthalmitis clinical features following minimally invasive removal of upper urinary tract calculi. Methods: Medical records of twelve patients (17 eyes) with endogenous endophthalmitis secondary to minimally invasive upper urinary tract calculus removal were retrospectively reviewed. Results: Diabetes mellitus was found in 7 patients (58%). 10 patients (83%) suffered from fever. The stone extraction and ocular symptom onset interval ranged from 2 to 22 days. All eyes presented as vitritis and fluffy yellow-white retinal exudates. Hypopyon was only found in 3 eyes (18%). 5 patients (42%) were misdiagnosed as uveitis which led to mismanagement. Ocular fluids were culture positive for only C. albicans in 12 eyes (71%). 10 of 12 eyes (83%) with silicon oil tamponade obtained a final BCVA≥0.05. Conclusions: C. albicans was the most common endogenous endophthalmitis pathogen after urinary calculus removal by minimally invasive surgery. Pars plana vitrectomy with silicon oil tamponade may be helpful to achieve a favorable visual outcome. Routine ophthalmologic evaluation by the uveitis or vitreoretinal specialist may be necessary within 2 weeks after the urological procedures.